El Clima de Aula desde la percepción de los Niños de grado 4 y5 a partir de la Clase Magistral y la Clase de Educación Fisica (2019)
The present investigation shows a micro ethnographic study on the perceptions of the master class and the class of physical education in the students of grade 4 and 5 of the I. E. Instituto Calarcá in the department of Quindío this study was carried out through observations, focal groups and interviews in depth where the information was collected, digitalized and by means of the ATLAS.TI was codified and categorized by saturation and significance, managing to structure three categories that give answer to the study carried out, allowing to establish how the master class oriented from traditional methods seeks to control the students. And as physical education stimulates knowledge, using the game as a means to fill the learner with joy they enjoy it, they enjoy generating emotions and positive feelings, taking to the development of their motor skills their creative part, their social and physical part since in all the recreational activities it contributes to their integral development.